Temporary Home Management of a Refractory Pleural Effusion with an Indwelling Catheter - Chiba, Tsukuru; Ishizuka, Mariko; Yoshikawa, Katsuhiro; Sueoka, Noriko; Yamamoto, Daigo (Gan to kagaku ryoho, 2019)
Pleurocentesis and pleurodesis are the common treatments for pleural effusion. However, most home-visit physicians usually hesitate to perform these treatments for patients confined at home. A 51-year-old woman developed breast cancer(ER+, HER2-)at the age of 39 years. She underwent a partial mastectomy of the right breast. Nine years later, metastatictumors in the lungs, and hilar and mediastinal lymph nodes were found. The patient was admitted to our hospital because of the progression of pleural effusion and dyspnea. On the day of admission, the aspiration catheter was placed in the left lung with continuous suction, but pleurodesis could not be performed as the left lung did not re-expand enough. As the patient requested to go home as soon as possible, she was discharged with the catheter in place. Three days after the discharge, the home-visit physician drained 340 mL of fluid through the catheter. Six days after the discharge, the patient was readmitted to the hospital with malaise and dyspnea, but no signs of complications associated with the indwelling catheter use were observed. The patient died 4 days after the readmission. This case suggests that draining fluid using an indwelling pleural catheter as a home-based healthcare measure is one of the simplest and safest options.